A review of electricity consumer behavioural change under sustainable energy management scheme - Mohamad Fani Sulaima; Nurul Fasihah Jumidey; Arfah Ahmad; Aida Fazliana Abdul Kadir; Mohamad Firdaus Sukri; Musthafah Mohd Tahir (Institute of Advanced Engineering and Science, 2022)
Many authorities launched their energy sustainability plan that involve the sustainable energy management scheme to improve energy efficiency. The sustainable energy management scheme consists of several measures to encourage energy efficiency in three primary energy consumers by pursuing implementation measures in the industrial, commercial, and residential sectors. Meanwhile, energy performance is quantifiable in energy efficiency and energy consumption become one of scheme measure aspects. In this review, the ASEAN Energy Management Scheme (AEMAS) was discussed as a regionally structured training and certification system for ASEAN Energy Managers. Besides that, Energy Management Gold Standard (EMGS) is AEMAS's first regional achievement certification for global excellence in energy management systems. Previous literatures exposed the key to energy efficiency goals is behavioural change, which means individual attitudes affect energy consumption.